Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2003
DOI: 10.1145/642611.642656
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive strategies and eye movements for searching hierarchical computer displays

Abstract: This research investigates the cognitive strategies and eye movements that people use to search for a known item in a hierarchical computer display. Computational cognitive models were built to simulate the visual-perceptual and oculomotor processing required to search hierarchical and nonhierarchical displays. Eye movement data were collected and compared on over a dozen measures with the a priori predictions of the models. Though it is well accepted that hierarchical layouts are easier to search than nonhier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…The experiment was run again by Hornof and Halverson (2003) to collect eye movement data that were used to evaluate the models in more detail. Sixteen people participated in each study.…”
Section: Cvc Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment was run again by Hornof and Halverson (2003) to collect eye movement data that were used to evaluate the models in more detail. Sixteen people participated in each study.…”
Section: Cvc Taskmentioning
confidence: 99%
“…Previous research suggests that a straightforward way to predict the observed number of fixations in a search task is to assume that two or three objects are processed per fixation (Hornof & Halverson, 2003). For this model, the EPIC visual-perceptual processor availability function was modified so that two or three words were processed per fixation regardless of density.…”
Section: Modeling What Is Perceived During a Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…e.g. [4]. To what extent can eyetracking contribute to the measurement of the five "E"s, efficiency, effectiveness, ease of learning, engagement, error tolerance [7]?…”
Section: Commercial Issuesmentioning
confidence: 99%
“…Blind users generally use screen readers to convert text and interaction controls on graphical user interfaces into synthetic speech output. Unlike sighted users, who often use non-linear and somewhat noisy approaches towards visual scanning of GUI interfaces (Hornof and Kieras, 1997;Hornof and Halverson, 2003), blind users of screen readers must rely on an inherently serial presentation of items: speech output does not lend itself well towards opportunistic scanning.…”
Section: Introductionmentioning
confidence: 99%